2014
DOI: 10.1017/s1368980014000482
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to nutritional guidelines in pregnancy: evidence from the Growing Up in New Zealand birth cohort study

Abstract: Objective: To determine adherence to nutritional guidelines by pregnant women in New Zealand and maternal characteristics associated with adherence. Design: A cohort of the pregnant women enrolled into New Zealand's new birth cohort study, Growing Up in New Zealand. Setting: Women residing within a North Island region of New Zealand, where onethird of the national population lives. Subjects: Pregnant women (n 5664) were interviewed during 2009-2010. An FFQ was administered during the face-to-face interview. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
42
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 32 publications
11
42
3
Order By: Relevance
“…Similarly, Blumfield et al found no evidence that women trying to conceive increased their consumption on nutrient rich foods such as FV [48]. In line with our results, several studies have found that only a small proportion of women consume the recommended number of vegetable servings per day, both pre-pregnancy [48] and during pregnancy [18, 35, 36, 44, 48, 49]. A national study from Australia showed that only 10% of pregnant women reported an intake of vegetables at or above recommendations [49].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, Blumfield et al found no evidence that women trying to conceive increased their consumption on nutrient rich foods such as FV [48]. In line with our results, several studies have found that only a small proportion of women consume the recommended number of vegetable servings per day, both pre-pregnancy [48] and during pregnancy [18, 35, 36, 44, 48, 49]. A national study from Australia showed that only 10% of pregnant women reported an intake of vegetables at or above recommendations [49].…”
Section: Discussionsupporting
confidence: 90%
“…Worldwide, higher socio-economic status tends to be associated with healthier food choices [40, 41]. In line with others, we found that a high intake of FV was associated with older age [8, 3235, 4244] and higher educational attainments [36, 42]. …”
Section: Discussionsupporting
confidence: 89%
“…The effectiveness of such strategies among women who have poor dietary quality but perceive their diets to be healthy may, however, be influenced by their willingness to increase their nutrition knowledge and understanding of a healthy diet, as suggested by Kearney and McElhone's (31) findings. As in previous research, women in our study reported avoiding or eating less high-listeria-risk foods during pregnancy and eating less fish and seafood (10,32) . Considering the following factors, it may be timely to reconsider how messages around fish intake during pregnancy are framed and delivered to the public: seafood has a relatively small impact on maternal blood Hg levels (accounting for approximately 9 % of the variation in whole-blood total Hg levels) (33) ; fish is rich in n-3 fatty acids and other essential nutrients such as iodine and vitamin D; and the positive associations found between fish intake during pregnancy and fetal neurodevelopmental outcomes (34) .…”
Section: Predictors Of Adherence To Dietary Guidelinessupporting
confidence: 70%
“…It is therefore concerning that suboptimal dietary quality has been consistently reported during pregnancy, reflecting poor adherence with dietary guidelines (6,7) . Moreover, studies from Australia and other developed countries including New Zealand, the UK, the USA and Canada have consistently shown poor adherence to food group recommendations during pregnancy (7)(8)(9)(10)(11)(12) .…”
mentioning
confidence: 99%
“…It has been asserted that midwives often lack the essential knowledge and skills to provide adequate and reliable nutrition advice to pregnant and lactating women on how to meet increased nutrient requirements during these critical and nutrient-demanding stages of their lives (Morton et al, 2014). Improving the quality of nutrition training of midwifery trainees is vital for building the necessary human resource capacity to provide effective nutrition education and counselling services in order to tackle the public health issue of malnutrition among vulnerable groups in Ghana (Yawson et al, 2017;Sodjinou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%